(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The Kummer and Dixon summation theorems essentially carry out the essential task of simplifying hypergeometric functions and double series. This essay will cover both the topic and the basic concept of hypergeometric functions as well as the understanding and importance of summation theorems in mathematical analysis. We explore the theorems made by Kummer and Dixon, show how their theorems are relevant and explain them by using particular examples involving the hypergeometric series. The other topic considered also is regarding the convergence of double series and we explain how these summation theorems can be used to make evaluation of them simpler. The comparative study exhibits the interworking nature between Kummer and Dixon telegrams to describe instances where their compounded application is advantageous. The lecture goes further in the topic and scrutinizes the application of these functions in multivariable hypergeometric as well as mathematics and physics. The method is also discussed. Besides this, the latest headway and unsolved issues are also highlighted with some prospective research targets being listed for the future. The Noether’s Theorem illuminates the concise relation between the affinity of the Dixon and Bernoulli Summation Theorems to maths and physics, therefore dispelling any misconceptions about its practicality. Our research aim is to provide the necessary spark for the discovery and invention in this area by developing new approaches and methods which will eventually lead to the growth of mathematical research and its practical applications.